2022
DOI: 10.1017/dmp.2022.52
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Wearing Face Mask in Public During COVID-19 Outbreak: A Qualitative Study

Abstract: Objective: Wearing face masks is believed to mitigate COVID-19 virus transmission by filtering respiratory droplets. This study was to explore the factors influencing wearing face masks in public in China during COVID-19 outbreak. Methods: This study was a qualitative semi-structured interview research design and was guided by the Protection Motivation Theory. Participants from Jiangxi Province China were interviewed via WeChat video call. Thematic analysis was used to analyze the data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
4
5
0
1
Order By: Relevance
“…This is in line with previous research (Armitage et al, 2023;Chen & Lei, 2022;He et al, 2022;White et al, 2022), and theories of health behaviour (Rogers, 1975). Similar to previous research, we found that rates of wearing a facemask were higher when it was legally obligated (Badillo-Goicoechea et al, 2021;He et al, 2022). For all but two psychological factors associated with wearing a facemask, these associations were significantly stronger when legal requirements were not in place, compared to when they were.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with previous research (Armitage et al, 2023;Chen & Lei, 2022;He et al, 2022;White et al, 2022), and theories of health behaviour (Rogers, 1975). Similar to previous research, we found that rates of wearing a facemask were higher when it was legally obligated (Badillo-Goicoechea et al, 2021;He et al, 2022). For all but two psychological factors associated with wearing a facemask, these associations were significantly stronger when legal requirements were not in place, compared to when they were.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous research (Armitage et al, 2023; Chen & Lei, 2022; He et al, 2022; White et al, 2022), and theories of health behaviour (Rogers, 1975). Similar to previous research, we found that rates of wearing a facemask were higher when it was legally obligated (Badillo‐Goicoechea et al, 2021; He et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Due to the unintrusive nature of this study, shoppers were not approached to collect these characteristics and other sociodemographic information (eg, age, income, education) known to be determinants of these preventive health behaviors. 13,17,19 As the pandemic evolves over time, the practice of these behaviors and public perceptions surrounding them may change. Therefore, these findings provide only a cross-section of observed practices and may not reflect true variability in outcomes at each establishment or over time.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified factors that predict favorable health behaviors during the COVID-19 pandemic, though many have focused on self-reported measures, qualitative methods, and assessed them while restrictions were in place. 13,[17][18][19] Few research studies have assessed COVID-19 preventive behaviors in community settings using observational methods. 20,21 Therefore, there is a need to fill this gap and further our understanding by conducting a cross-sectional study to evaluate current COVID-19 preventive behaviors among the public in the Canadian context, especially in the absence of COVID-19 regulatory health policies.…”
mentioning
confidence: 99%